A Maxim of Violation as a Portray of Personality in the Novel The Three Button Trick and Other Stories by Nicola Barker - Evin Istiqomah Arisandy; Jepri Jepri; Adi Prautomo (Faculty of Letters Universitas Balikpapan, 2019)
This research explores how the maxim violation can portray personality of characters inthe novel The Three Button Trick and Other Stories by Nicola Barker. The researchobjectives are; to find out the types of maxim violations appear in the novel and to knowhow maxim violation can portray personality of the characters in the novel The ThreeButton Trick and Other Stories by Nicola Barker. The theories used in this research aremaxim violation introduced by Paul Grice as the main theory conducted to explain aboutthe maxim violation phenomena. Besides that, Personality Traits Theory as known as ‘ FiveFactor Theory’ by McCrae and Costa to depict the personality owned by the characterswho violate maxims in the novel The Three Button Trick and Other Stories by NicolaBarker. As the result of the research, the researcher found that maxim violation, behaviorsand personality are interchangeable and interconnected. At the time a speaker performsmaxim violation by which generate other interpretation of what it is said withincommunication, the utterance apparently portrays the speaker’s personality throughout themeaning, true intention and behavior it is conveyed.